Human Lung Mast Cells Impair Corticosteroid Responsiveness in Human Airway Smooth Muscle Cells - Alzahrani, Abdulrahman; Hakeem, Jameel; Biddle, Michael; Alhadian, Fahad; Hussain, Aamir; Khalfaoui, Latifa; Roach, Katy M.; Tliba, Omar; Bradding, Peter; Amrani, Yassine (Frontiers in Allergy, 2021)
The mechanisms underlying corticosteroid insensitivity in severe asthma have not been elucidated although some indirect clinical evidence points toward a role of mast cells. Here, we tested the hypothesis that mast cells can drive corticosteroid insensitivity in airway smooth muscle cells, a key player in asthma pathogenesis. Conditioned media from resting or FcεR1-activated human lung mast cells were incubated with serum-deprived ASM cells (1:4 dilution, 24 h) to determine their impact on the anti-inflammatory action of fluticasone on ASM cell chemokine expression induced by TNFα (10 ng/ml). Conditioned media from FcεR1-activated mast cells (but not that from non-activated mast cells or control media) significantly reduced the ability of 100 nM fluticasone to suppress ASM TNFα-dependent CCL5 and CXCL10 production at both mRNA and protein levels. In contrast, fluticasone inhibition of CXCL-8 production by TNFα was still preserved in the presence of activated mast cell conditioned media. Transcriptomic analysis validated by individual qPCR assays revealed that activated mast cell conditioned media dramatically reduced the number of anti-inflammatory genes induced by fluticasone in ASM cells. Our study demonstrates for the first time that conditioned media from FcεR1-activated mast cells blunt the anti-inflammatory action of corticosteroids in ASM cells by altering their transactivation properties. Because infiltration of mast cells within the ASM bundles is a defining feature of asthma, mast cell-derived mediators may contribute to the glucocorticoid insensitivity present in severe asthma.